Rethinking statehood in Palestine : self-determination and decolonization beyond partition - Farsakh, Leila; Farsakh, Leila (New directions in Palestinian studies ;, 2021)
"The quest for an inclusive and independent state has been at the center of the Palestinian national struggle for a very long time. This book reexamines this quest by exploring the meaning of Palestinian statehood and the challenges that face alternative models to it today. Rethinking Statehood in Palestine gives prominence to a young set of diverse Palestinian scholars, both men and women, to show how notions of citizenship, sovereignty, and nationhood are being currently rethought within the broader context of decolonization. Bringing forth critical and multifacetted engagements with what Palestinian self-determination entails within a larger regional context, this book sets the terms of debate for the future of Palestine beyond partition"--